2008
DOI: 10.1104/pp.108.126136
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Interference with AtTCP20 Function Induces Severe Plant Growth Alterations and Deregulates the Expression of Many Genes Important for Development  

Abstract: AtTCP20 is a transcription factor belonging to the Arabidopsis (Arabidopsis thaliana) TCP-P subfamily, characterized by its capacity to bind to site II motifs (TGGGCY). Our aim was to understand the role of AtTCP20 in plant development. The expression pattern of a translational fusion of PromTCP20:CDS20∷GUS∷GFP suggested a function for AtTCP20 in several plant organs and stages of development. The role of AtTCP20 was challenged in planta by inducing expression of AtTCP20 proteins fused with either a transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
130
0
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(144 citation statements)
references
References 66 publications
(90 reference statements)
6
130
0
6
Order By: Relevance
“…It has been suggested that TCP proteins may function either as transcriptional activators or repressors, depending on their interactions with other proteins (Hervé et al, 2009). As the GhTCP14-overexpressing plants phenocopied auxin distribution mutants such as pin2, we analyzed the expression of PIN2 and other auxin-related genes in the transgenic plants and found that the expression of several auxin-related genes was either increased or decreased.…”
Section: Ghtcp14 Is a Dual-functional Transcription Factormentioning
confidence: 99%
See 3 more Smart Citations
“…It has been suggested that TCP proteins may function either as transcriptional activators or repressors, depending on their interactions with other proteins (Hervé et al, 2009). As the GhTCP14-overexpressing plants phenocopied auxin distribution mutants such as pin2, we analyzed the expression of PIN2 and other auxin-related genes in the transgenic plants and found that the expression of several auxin-related genes was either increased or decreased.…”
Section: Ghtcp14 Is a Dual-functional Transcription Factormentioning
confidence: 99%
“…The distinctive activities of GhTCP14 may depend on its interaction with other proteins (Hervé et al, 2009).…”
Section: Ghtcp14 Is a Dual-functional Transcription Factormentioning
confidence: 99%
See 2 more Smart Citations
“…In Arabidopsis, the same Site II sequence GGCCCA and slight variations are bound by a family of transcription factors known as the TCP family, which share sequence similarity with rice PCF1/PCF2 (reviewed in Martín-Trillo and Cubas, 2010). The Arabidopsis TCP proteins, and their binding motif, have been described on many occasions as regulatory elements involved in regulating genes required for cell cycle control, growth, and development (Tré mousaygue et al, 2003;Li et al, 2005;Gonzalez, 2005, 2006;Hervé et al, 2009;Pruneda-Paz et al, 2009). To our knowledge, there have been no previous reports of the involvement of calcium signaling upstream of this cis-element or its transcription factors.…”
Section: Imposed [Ca 2+ ] C Elevations Are Capable Of Inducing Signifmentioning
confidence: 99%